Possibility to Influence Treatment of Open Tibial Fracture by Negative Pressure Wound Therapy - Miroslav Budoš, MUDr.; Radek Veselý, MUDr. (International Journal of Surgical Techniques, 2019)
Modern medicine gives treatment options even in cases, where this has not been possible in the past. We want to present how negative pressure wound therapy (NPWT) helps in limb salvage. The case report brings our insight and experience on how to be successful with NPWT. We present a high-energy injury with an open tibial fracture IIIB according to Gustillo-Anderson classification 11. NPWT is an excellent option to treat extensive soft tissue injury. NPWT is also beneficial in the application of the dermoepidermal graft as we have found. We can confirm that this therapy contributed to a faster healing of soft tissues compared to classical wound healing.
Keywords: high energy injury; open tibial fractures; soft tissues injury; negative pressure wound therapy; limb salvage; osteosynthesis; dermoepidermal graft